2020
DOI: 10.1021/acsaelm.0c00304
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress on Energy-Related Applications of HfO2-Based Ferroelectric and Antiferroelectric Materials

Abstract: Ferroelectric and antiferroelectric materials are promising options for energy-related (such as energy harvesting, energy storage, IR detection, and refrigeration) and memory applications (such as ferroelectric random-access memory (FeRAM) and ferroelectric field-effect transistor (FeFET)). In the past, several classes of materials (such as polymers, ceramics, single crystals, and glasses) have been studied for these properties. However, because of a large deposition thickness (in micrometers or larger), these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 151 publications
0
57
0
Order By: Relevance
“…[1] AFEs are a unique class of materials which, due to their nonlinear dielectric and strain characteristics, are useful for energy storage, infrared sensing, active electronic cooling, piezoelectric devices, and electronic memories. [2][3][4] Double fluorite-structured materials based on DFT calculations as well as experimental evidence. [3,6,20,23] The stabilization of the FE o-phase has been the focus of many investigations due to the interest in using FE HfO 2 -based thin films for CMOS compatible memory applications, such as FE random access memory and FE field effect transistors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] AFEs are a unique class of materials which, due to their nonlinear dielectric and strain characteristics, are useful for energy storage, infrared sensing, active electronic cooling, piezoelectric devices, and electronic memories. [2][3][4] Double fluorite-structured materials based on DFT calculations as well as experimental evidence. [3,6,20,23] The stabilization of the FE o-phase has been the focus of many investigations due to the interest in using FE HfO 2 -based thin films for CMOS compatible memory applications, such as FE random access memory and FE field effect transistors.…”
Section: Introductionmentioning
confidence: 99%
“…[3,5] Underlying electric field-induced FE structural phase transitions are hypothesized to be responsible for generating the distinctive features of antiferroelectricity in the fluorite material system, yet little is known about how to best exploit such phase transitions in fluorites. [4,6] Alternative theories of AFE-like behavior, such as oppositely imprinted FE domains and paraelectric-to-paraelectric phase transitions, need to be evaluated since the approach to achieve superior AFE device performance will depend on the underlying cause of macroscopic antiferroelectricity. [7][8][9][10] Due to the simplicity of controlling the film thickness, the size effect may be easily leveraged to influence and gain a better understanding of antiferroelectricity in ZrO 2 , but previous film thickness studies on ZrO 2 and Hf 1−x Zr x O 2 have not quantified the size-effect influence on supercapacitor performance.…”
mentioning
confidence: 99%
“…Similar temperatureinduced FE phase transformations were also reported in HZO solid systems and Al-doped HfO 2 films [20,74] . This phenomenon is very useful for energy-related applications in nanoscale devices, such as electrocaloric cooling devices [31,51,139,140] . Hoffmann et al [23] reported that giant pyroelectric coefficients up to 1300 μC/(m 2 K) were achieved due to the temperature-induced structural transition.…”
Section: Temperaturementioning
confidence: 99%
“…[ 47 ] A recent review discussing the performances of energy conversion and their dependence on temperature and doping concentrations is ref. [48]. The energy storage density (ESD) is a parameter relevant for ferroelectric materials.…”
Section: Energy Harvesting Using Hfo2‐based Ferroelectricsmentioning
confidence: 99%
“…In ref. [48], it is noted that antiferroelectrics show a double hysteresis loop and lower losses compared to ferroelectrics, and thus attaining higher ESD.…”
Section: Metal Cr/aumentioning
confidence: 99%